Enterprise architecture at work : modelling, communication, and analysis - Lankhorst, Marc. (Dordrecht ; New York : Springer, 2009)
The book tries to describe and control an organisation's structure, processes applications, systems and techniques in an integrated way.
Includes bibliographical references (p. [335]-345) and index.
rua 28/08/2013
Loans
Keywords: Industrial organization; Industrial management; System design; Management information systems; Strategic planning